Business Model Canvas for Internet of Things Application on Hydroponic in Tangerang - Dellih Wijaya; Riki riki; Benny Daniawan; Annisa Lorenza (bit-Tech, 2024)
Internet of Thing (IoT) in hydroponics was developed to monitor and control the hydroponic environment for efficiency and effectiveness with maximum results purpose. Many papers expose about IoT application on hydroponic, this article completed it with business model so it will sustain as valuable business especially in Tangerang Banten Indonesia. It is interesting and necessary to analyze the business model, so that this valuable system of the solution can sustain and growth, also proper for the big picture purpose. Of seventeen (17) goals SDGs, hydroponic using IoT application is related to solving point number two (2) about zero hunger and point number thirteen (13) about climate action. This paper uses qualitative descriptive methodology which analyzes and provides points of BMC for IoT application on hydroponic. The result of this paper found that BMC is proper tool to analyze and describe business model for IoT of hydroponic. Then this paper also finds there are several points of revenue streams with some different customer segments, support from hydroponic community, and some collaboration with key partners is needed, which means the business cannot stand alone. This paper has limitations which could be further interesting topics for the next paper.